Textual cacophony : online video and anonymity in Japan - Johnson, Daniel, 1982- (Cornell East Asia series, 2023)
"Textual Cacophony discusses online media in Japan, with a focus on how anonymity and asynchronous media interfaces impact the aesthetic and cultural practices of users of Niconico, 2channel, and related social media platforms"--